1-3x(x-1)=

Simple and best practice solution for 1-3x(x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-3x(x-1)= equation:


Simplifying
1 + -3x(x + -1) = 0

Reorder the terms:
1 + -3x(-1 + x) = 0
1 + (-1 * -3x + x * -3x) = 0
1 + (3x + -3x2) = 0

Solving
1 + 3x + -3x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
-3 the coefficient of the squared term: 

Divide each side by '-3'.
-0.3333333333 + -1x + x2 = 0

Move the constant term to the right:

Add '0.3333333333' to each side of the equation.
-0.3333333333 + -1x + 0.3333333333 + x2 = 0 + 0.3333333333

Reorder the terms:
-0.3333333333 + 0.3333333333 + -1x + x2 = 0 + 0.3333333333

Combine like terms: -0.3333333333 + 0.3333333333 = 0.0000000000
0.0000000000 + -1x + x2 = 0 + 0.3333333333
-1x + x2 = 0 + 0.3333333333

Combine like terms: 0 + 0.3333333333 = 0.3333333333
-1x + x2 = 0.3333333333

The x term is -1x.  Take half its coefficient (-0.5).
Square it (0.25) and add it to both sides.

Add '0.25' to each side of the equation.
-1x + 0.25 + x2 = 0.3333333333 + 0.25

Reorder the terms:
0.25 + -1x + x2 = 0.3333333333 + 0.25

Combine like terms: 0.3333333333 + 0.25 = 0.5833333333
0.25 + -1x + x2 = 0.5833333333

Factor a perfect square on the left side:
(x + -0.5)(x + -0.5) = 0.5833333333

Calculate the square root of the right side: 0.763762616

Break this problem into two subproblems by setting 
(x + -0.5) equal to 0.763762616 and -0.763762616.

Subproblem 1

x + -0.5 = 0.763762616 Simplifying x + -0.5 = 0.763762616 Reorder the terms: -0.5 + x = 0.763762616 Solving -0.5 + x = 0.763762616 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = 0.763762616 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = 0.763762616 + 0.5 x = 0.763762616 + 0.5 Combine like terms: 0.763762616 + 0.5 = 1.263762616 x = 1.263762616 Simplifying x = 1.263762616

Subproblem 2

x + -0.5 = -0.763762616 Simplifying x + -0.5 = -0.763762616 Reorder the terms: -0.5 + x = -0.763762616 Solving -0.5 + x = -0.763762616 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = -0.763762616 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = -0.763762616 + 0.5 x = -0.763762616 + 0.5 Combine like terms: -0.763762616 + 0.5 = -0.263762616 x = -0.263762616 Simplifying x = -0.263762616

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.263762616, -0.263762616}

See similar equations:

| 8x-7=9x+12 | | -147=-3+8a | | 4-6x=12x-7 | | 14(x^2)(y^2)+9xy-18=0 | | a/7+4=2 | | 5p-30=12 | | -1=5-4x-10-x+45 | | 4b+16=35 | | 3=-3k+9 | | 2(m+3)+1=23 | | 5x-10x+14=-3x+6 | | 3+y/4=1.95 | | 2t+38=5(t+1) | | x+4+6x-6=180 | | 23x-8-14x=21 | | x+5+x=10 | | -2(x-4)=-16 | | x+4=6x-6 | | 0=3x-9-4x | | 5x+-3=-18 | | 14+8a=4a-10 | | X+3y=60 | | 7c+28=105 | | 16x-9x-15=13 | | 4c-13c-6c=-49 | | 35x^2y^2+9xy+-2=0 | | 2(6w-9)-6=24-12w | | 5x-2=15x+112 | | 5-2z=17 | | 15r+6s-11t+r-9s+t-2s+5r-2t-r= | | 4+x+7=-36 | | 28-0.3y=0.7t-12 |

Equations solver categories